Peran Guru PAI dalam Pengembangan Kurikulum Berbasis Kompetensi Abad ke-21 dan Literasi Digital di SD Negeri 4 Purwodadi Kabupaten Grobogan - Nur Wijayat; Sari Hernawati (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2025)
The 21st century demands fundamental transformation in all aspects of education, including Islamic Religious Education (PAI). The PAI curriculum is no longer sufficient to only equip students with normative knowledge, but must integrate crucial 21st-century competencies such as critical thinking, collaboration, communication, and creativity (4C), as well as essential digital literacy skills. This article analyzes the vital role of PAI teachers as the main agents in the development and implementation of PAI curriculum that is responsive to the demands of this era. Using a literature review method and a qualitative-descriptive approach, this article identifies that PAI teachers are required to be innovative learning designers, facilitators of 4C competency development, digital literacy agents, developers of adaptive teaching materials, and evaluators of competency-based learning. The results of the discussion show that the main challenges include a shift in the teaching paradigm, effective technology integration, and management of the rapid flow of information. Therefore, increasing the capacity and professionalism of PAI teachers in a sustainable manner is a necessity to produce a generation of Muslims who are not only noble, but also adaptive, critical, and competitive in the digital era.